A New Method for Determining the Composition of Core–Shell Nanoparticles via Dual‐EDX+EELS Spectrum Imaging. (22nd July 2016) - Rossouw, David; Knappett, Benjamin R.; Wheatley, Andrew E. H.; Midgley, Paul A.
Abstract : Simultaneously acquired microanalytical X‐ray and electron energy loss signals are obtained from a bimetallic core–shell nanoparticle system (FePt@Fe3 O4 ). The signals are decomposed using independent component analysis and the extracted components are used to separately quantify the composition of the spatially overlapping core and shell phases in the nanoheterostructure. The utilization of the complementary strengths of energy dispersive X‐ray and electron energy‐loss spectroscopy microanalysis has enabled the quantification of both light and heavy elements in a single spectrum image acquisition. Abstract : A new method of determining the composition of spatially overlapping phases in a core–shell nanoparticle system is described. The technique involves the decomposition of simultaneously acquired microanalytical X‐ray (green) and electron energy loss signals (red) by independent component analysis, enabling the separation of spatially and spectrally overlapping signal components from both light and heavy elements.